Exponential consensus of non‐linear stochastic multi‐agent systems with ROUs and RONs via impulsive pinning control. Issue 2 (1st January 2017) - Ren, Hongwei; Deng, Feiqi; Peng, Yunjian; Zhang, Bo; Zhang, Chaolong
Abstract : Exponential consensus of non‐linear stochastic multi‐agent systems is investigated. The authors consider a class of non‐linear stochastic multi‐agent systems that are subject to time‐varying delays, randomly occurring uncertainties and randomly occurring non‐linearities. Impulsive pinning control algorithms are proposed to ensure that follower agents track the leader under a fixed topology. On the basis of the Lyapunov function and the Halanay differential inequality of impulsive dynamical systems, we derive sufficient conditions for the globally exponential consensus of the multi‐agent systems. Finally, numerical simulations demonstrate the effectiveness of the proposed theoretical results.